American antifa : the tactics, culture, and practice of militant antifascism - Vysotsky, Stanislav 1973- (Routledge studies in fascism and the far right, 2021)
Introduction -- Fascists and antifascists : a countermovement overview -- Fascist and antifascist tactics -- "Sometimes anti-social, always antifascist" : antifa culture -- Fascist threat and antifascist action -- The anarchy police (revisited) : a critical criminology of antifa -- Antifa unmasked : a sociological and criminological understanding -- Appendix: Against methodology : ethnography, autoethnography, and the intimately familiar.